Implementasi Aplikasi Pelayanan Administrasi berbasis Digital (Sipakde) dalam Meningkatkan Kepuasan Masyarakat di Kecamatan Depok Sleman - Mohamad Kusnandar Pamungkas; Sugiyanto Sugiyanto (SENTRI: Jurnal Riset Ilmiah, 2026)
Digital transformation through e-government has become a crucial strategy for delivering public services that are effective, efficient, and transparent. The Depok District Government in Sleman Regency has developed the Depok Sub-district Administrative Service Information System (Sistem Informasi Pelayanan Administrasi Kapanewon Depok – SIPAKDE) as an innovation to improve public service delivery. This study aims to analyze the implementation of the SIPAKDE application in enhancing public satisfaction and to identify the supporting and inhibiting factors affecting its implementation. A descriptive qualitative research design was employed, with data collected through in-depth interviews, direct observation, and documentation. Informants were selected using purposive sampling. Data were analyzed using the Miles and Huberman interactive model and validated through triangulation techniques. Based on George C. Edward III’s policy implementation framework, the findings indicate that the dimensions of communication, resources, disposition, and bureaucratic structure have generally been implemented effectively. However, communication effectiveness remains constrained by the community’s low level of digital literacy, while resource-related challenges occasionally arise due to network connectivity disruptions. The main supporting factors include strong leadership commitment, competent public officials, and well-defined standard operating procedures (SOPs). The implementation of SIPAKDE has positively influenced public satisfaction by improving service accessibility, accelerating service delivery, reducing service costs, and enhancing process transparency. This study concludes that the successful implementation of digital bureaucracy depends not only on technological readiness but also on strengthening users’ digital literacy to maximize the benefits of e-government services.